Les systèmes d'élevage des moutons en Nouvelle-Galles du Sud (Australie) - Grégoire Dupont; Roger Compère (Biotechnologie, Agronomie, Société et Environnement, 1997)
Sheep breeding systems in New South Wales (Australia). Three sheep breeding farms representative of each of the three climatic regions of New South Wales semi-arid, sub-humid and humid have been studied in order to characterize from a technico-economic point of view the breeding systems which are suited to the particularities of climate and soil. Grass intensification depends directly on the annual distribution patterns of rainfall but also on soil quality which varies according to relief; clayey, rich and deep in valleys and alluvial plains; sandy, poor and superficiel on bills. The degree of intensification and diversification of sheep production obeys the saure criteria: from the production of fine wool only in semi-arid arecs with the Merino breed and to more and more advanced crosses with British breeds specialized in the production of early maturing lambs as rainfall becomes favourable to fodder production. The farming entreprises are of family type, production costs are particularly low thanks to the perfect knowhow of breeding techniques by motivated and experienced breeders working with field techniciens. This enables profit to be made despite the current low prises for animais and wool.